Phytoremediation of Cadmium in river water by Ceratophyllum demersum - Hind J. Al-Ubaidy; Khalid A. Rasheed (World Journal of Experimental Biosciences, 2015)
The current study included an assessment of the ability of Ceratophyllum demersum Phytoremediation of cadmium in accumulative concentration by measuring the heavy metal in the tissues of the plant to check the ability of C. demersum to reduce or eliminate the harmful and toxic effect, which resulting from this type of pollutants in the most important ecosystem. In present study the plant was grown in natural conditions for two months and treated to two concentrations of cadmium (3.714, 4.952 mg/l). The samples of water and a certain weight of the plant were taken before and after treating with cadmium chloride in order to estimate the level of cadmium in these samples before and after treatment. The residual amount of cadmium in the water and also in the plant has also been calculated at different time intervals (3, 6 and 9 days). The present study showed that cadmium accumulated rapidly in the plant and increased dramatically with time, thus the highest level of cadmium was observed at day nine. C. demersum showed high ability to remove cadmium and was at the ninth day of the experiment and that was 1.53, and 1.089 mg /l) when exposed to 3.714, 4.952 mg /l of cadmium respectively. The current study proved strongly the ability of C. demersum to eradicate the cadmium in ecosystem.
Keywords: Cadmium, Ceratophyllum demersum, Phytoremediation, River